EFFECTS OF QUERCETIN AS AN EXTENDER-ADDITIVE ON CRYOPRESERVATION OF GIR BULL SEMEN - PRAJAPATI, S G; VALA, K B; SOLANKI, G B; SINGH, V K; CHAVDA, B P (The Indian Journal of Animal Reproduction, 2021)
The present investigation was undertaken on semen of four mature healthy Gir bulls (4-6 years) maintained identically on University farm, Junagadh (India) during hot summer months. Semen collected using AV, soon after routine evaluation, was diluted with extender Andromed containing Quercetin as an antioxidant, viz. 0 μM (control), 50 μM, 100 μM and 200 μM level, filled in French medium straws and frozen with conventional system. The samples were evaluated for sperm quality parameters and oxidative markers, viz., LPO/MDA and GST activity in seminal plasma at per-freeze (post-equilibrium) and post-thaw stage of cryopreservation. The mean pre-freeze values of individual sperm motility, viability, HOS reactive sperm and acrosomal integrity (75.58±1.07, 77.88±0.99, 65.88±0.31 and 81.46±0.29 %, respectively) in 100 μM Quercetin group were significantly (p<0.05) higher with lower sperm abnormality, malondialdehyde (MDA) level and GST activity (15.21±0.66%, 6.99±0.12 μM and 20.23±2.29 nmol/ml/ min) as compared to those of 50 μM and 200 μM Quercetin and control groups. At post-thaw stage also 100 μM Quercetin group showed similar trend with significantly higher sperm motility, viability, HOS reactivity and acrosomal integrity (59.58±0.48, 62.13±0.89, 59.04±0.88 and 73.04±0.45 %, resp.) and lower sperm abnormality, malondialdehyde (MDA) level and GST activity (20.96±0.48%, 7.25±0.57 μM and 38.70±3.65 nmol/ml/min) as compared to those of 50 μM and 200 μM Quercetin and control groups. All the sperm quality and oxidative stress parameters were better in 100 μM Quercetin group at both pre-freeze and post-thaw stage of cryopreservation. It is thus concluded that 100 μM is the most appropriate concentration of Quercetin as an additive to improve the quality parameters of cryopreserved semen of Gir bulls.